Pengaruh Promosi terhadap Keputusan Pembelian Konsumen Sepatu pada PT. Sepatu Bata Tbk (Studi Kasus Pada Simpang Bata Kota Jambi) - Hendri Gunawan (Universitas Batanghari Jambi, 2020)
The purpose of this research is to know how promotions and purchasing decisions are at PT. Sepatu Bata Tbk and to know the influence between the promotion to the purchase decision of PT. Sepatu Bata Tbk. This research used a multiple linear regression analysis tool used to figure out the direction of the relationship between the independen variable of the dependen variabel. Then, to answer the purpose of this research is used the t-test and koefisien determinasi. PT. Sepatu Bata Tbk is one of the stores that markets brick brand shoes in the city of Jambi. Brick shoes brand has been famous and has a good market share, shoes are sold with a variety of variants. The average answer score of 247.1 means that the promotion is assessed not consented by consumers. Consumers place non-media communication indicators as the highest with an average score of 256. While media communication indicator is rated as the lowest with a score of 234.3. The average score of 334.5 answers means that a purchase decision is assessed by consumers. Consumers put the indicator of product choice as the highest with an average score of 372. While the brand choice as the lowest with a score of 348.6.Based on the hypothesis tests it can be seen that the promotion has a positive effect on purchasing decisions. This is evidenced by the value of the larger counting T with the table T value (6.479 > 1.661) and with a significance rate smaller than the α value (0.05) which is 0.000. The value of R Square 0.518 means the promotion is only able to influence the purchase decision at PT. Sepatu Bata Simpang Bata Branch of Jambi City of 51.8% and the remaining 48.2% is influenced by other variables not examined in this study.